Theory and experimental verification of a double sliding isolator with variable curvature. (1st July 2021) - Lu, Lyan-Ywan; Huang, Han-Wei; Wu, Yang; Wang, Shao-Jou
Highlights: DSIVC is a passive adaptive sliding isolator with variable mechanical property. DSIVC have dual variable-curvature sliding surfaces and a slider in between. Bi-directional force–displacement formula of DSIVC was derived in a matrix form. A prototype DSIVC with softening-and-then-hardening property was tested. Test result demonstrates the feasibility and adaptability of DSIVC technology. Abstract: A seismic isolation system with traditional sliding bearings, such as friction pendulum isolators (FPIs), is typically a low-frequency system with constant isolation stiffness. Although this type of isolation system may perform well in a regular earthquake, it may incur excessive isolation displacement in earthquakes with strong long-period components, such as near-fault earthquakes. In order to enhance the isolation performance and prevent an excessive isolation response due to long-period ground motions, in this study, a new type of passive adaptive sliding isolator called a double sliding isolator with variable curvature (DSIVC) is studied both theoretically and experimentally. A DSIVC isolator is mainly composed of an upper and a lower variable-curvature sliding surface and a slider sandwiched between the two sliding surfaces. Due to the variable curvature feature, the isolator stiffness of the DSIVC can vary along with the isolator displacement. Therefore, the DSIVC has an adaptive property that may help avert the resonant-like response exerted by a near-fault earthquake. Furthermore, since a DSIVC has two sliding interfaces, it can double the isolator displacement capacity with a given isolator size, so both the manufacturing costs and installation space of the isolators can be reduced. In this paper, a systematic formula that describes the bi-directional force–displacement relationship of a general DSIVC was comprehensively derived. The formula, in a matrix form, satisfies force equilibrium, constitutive law, and geometric compatibility conditions simultaneously. Also, in order to experimentally verify the derived formula, a cyclic element test with uni- and bi-directional excitations was conducted on a prototype DSIVC. The experimental results of this study not only verify the correctness of the derived formula, but also demonstrate the feasibility and adaptability of the DSIVC isolation technology.